Assistance in the Use of Asset Inventory Management Information Systems in Sukaraja Village - hidayat, ramdhani; Sidiq, Purnomo; Zanjabila, Haiva Nabila (Fakultas Kewirausahaan Universitas Garut, 2023)
Abstract Information technology is currently experiencing rapid growth. Its impact is significant in supporting efficiency and operations in various sectors such as education, business, and government administration. Governments have adopted various information systems that improve the effectiveness of their administrative processes. However, the government at the Sukaraja Village Office still has not implemented an asset inventory management information system in managing its asset inventory data or in other words, it still relies on a manual method that is based on spreadsheets, causing limitations in efficiency, accuracy, and easy access to information. This study uses the prototype method to facilitate system development that can be continuously adjusted to user needs and feedback. The stages of this research involve analyzing user needs, designing the system, developing a prototype, implementing it, and conducting evaluations. Creating this asset inventory management information system will offer benefits in record-keeping, maintaining, and monitoring asset inventory, as well as increasing the availability of accurate and fast information for users. Keywords: Sukaraja Village Office, Asset Inventory Management Information System, Prototype Method